2009
DOI: 10.1158/0008-5472.sabcs-09-2017
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor RNA Activator Protein (SRAP): A Potential New Prognostic Marker for Estrogen Receptor-Positive/Node-Negative/Younger Breast Cancer Patients.

Abstract: Purpose: The steroid receptor RNA activator (SRA) is a functional RNA suspected to participate in the mechanisms underlying breast tumor progression. This RNA is also able to encode for a protein, SRAP, whose exact function remains to be determined. Our aim was to assess, in a large breast cancer cohort, whether levels of this protein could be associated with outcome or established clinical parameters.Experimental Design: Following antibody validation, we have assessed SRAP expression by tissue-microarray (TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…Western Blot and immunofluorescent microscopy: Western Blot and Immunofluorescent Microscopy were performed as previously described (7). …”
Section: Case Reportsmentioning
confidence: 99%
“…Western Blot and immunofluorescent microscopy: Western Blot and Immunofluorescent Microscopy were performed as previously described (7). …”
Section: Case Reportsmentioning
confidence: 99%
“…Total cell lysates were separated on 10% SDS-PAGE and analyzed by Western blotting as described previously [23].…”
Section: Western Blottingmentioning
confidence: 99%
“…As its RNA counterpart, SRAP physically interacts in vitro with several transcription factors [5,21] and might co-activate or repress their action depending on the promoter and the cellular context considered [5,21,22]. We have previously observed that in specific breast cancer subgroups, high levels of SRAP were associated with poor patients survival [23,24]. This suggests that SRAP could be a potential prognostic marker and/or contribute to increasing tumor aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted to be upregulated in tumors compared with normal tissues, such as breast cancer (Murphy et al 2000 ) and ovarian cancer (Hussein-Fikret and Fuller 2005 ). By tissue-microarray analysis of 372 breast tumors, SRAP levels signifi cantly correlated with ER+, PR+, and older (age >64 years) patients, and higher SRAP expression in ER+, PR+, or younger (age ≤64 years) patients correlated with a worse survival rate (Yan et al 2009 ). By tissue-microarray analysis of 372 breast tumors, SRAP levels signifi cantly correlated with ER+, PR+, and older (age >64 years) patients, and higher SRAP expression in ER+, PR+, or younger (age ≤64 years) patients correlated with a worse survival rate (Yan et al 2009 ).…”
Section: Sramentioning
confidence: 99%